Interactive Pancasila Based Anti Bullying Modules Foster Elementary Student Empathy Outcomes: E-Modul Interaktif Anti Perundungan Berbasis Pancasila Mengembangkan Empati Siswa Sekolah Dasar - Mahyaya Nur; Jamaluddin Arifin; Ade Irma Suriani (Academia Open, 2026)
General Background Elementary education serves as a fundamental phase for character formation, yet many schools face severe challenges with aggressive behaviors among young learners. Specific Background At SDIT Al-Fadiyah in Gowa Regency, lower elementary students demonstrate limited social awareness and emotional regulation, frequently engaging in unrecognized aggressive actions during daily peer interactions. Knowledge Gap Despite the critical need for contextual moral education, current pedagogical practices predominantly rely on conventional lecture methods and lack interactive digital materials tailored to instil early social awareness. Aims This study develops a valid, practical, and functional digital tool integrating the Just and Civilized Humanity principle to advance academic achievement and social understanding among second-grade cohorts. Results Utilizing the ADDIE research and development model with 25 participants, the developed digital framework achieved exceptional validity and practicality ratings exceeding 96 percent across all expert assessments. Following implementation, cognitive test scores advanced from 78.12 to 95.00, and observational metrics progressed from 73.75 percent to 96.50 percent, supported by a significant Wilcoxon test result and a high N-Gain coefficient. Novelty This research distinctly integrates foundational civic principles into an interactive digital framework to specifically address early childhood aggression and cultivate structured prosocial development. Implications Educational institutions should adopt these contextual digital tools within civic curricula to sustainably foster inclusive, safe, and respectful school environments. Highlights Digital civic learning materials demonstrate exceptional validity and instructional practicality across expert evaluations. Integrating moral values significantly elevates cognitive achievement scores in early childhood education. Contextual multimedia simulations successfully promote prosocial behavior and emotional regulation among young learners. Keywords Digital Civic Education; Prosocial Behavior; Interactive Learning Media; Character Formation; Early Childhood Aggression